Idiot. 3 x 3 = 12. Like Comment Share El 393 people like this, LP M shares CO View previous comments I killall, mi "Like minutes ago Li q I its 1 you do first t yupp
x
FJ is now mobile friendly. Try it out on your mobile browser!
Click to expand

Idiot

Tags: yupp
Like Comment Share
El 393 people like this,
LP M shares
CO View previous comments
I killall, mi "Like
minutes ago Li
q I its 1 you do first then multiply the
2 by the sum of that owning you 6 which then makes
it are
q minutes ago . Like
q minutes ago . Like
2 minutes ago via mobile . Like
E 2 minutes ago via mobile . Like
Write an comment. ..
...
  • Recommend tagsx
+423
Views: 21251
Favorited: 18
Submitted: 03/22/2013
Share On Facebook
Add to favorites Subscribe to dagrizzlybear submit to reddit

Comments(427):

[ 427 comments ]
What do you think? Give us your opinion. Anonymous comments allowed.
#54 - thesoulless (03/23/2013) [+] (2 replies)
Instructions not clear enough, got dick stuck in calculator.
Instructions not clear enough, got dick stuck in calculator.
User avatar #400 - Snookbone (03/23/2013) [-]
Well in Britain our equivalent of PEMDAS is BIDMAS, Brackets (or parentheses), Indices, Division&Multiplication, Addition&Subtraction.

Therefore, you deal with the brackets first, and then divide.

Ergo, 2(1+2)= 6
6/6=1
#164 - crilleballe (03/23/2013) [+] (4 replies)
6 / 2 ( 1 + 2 ) = x     <=>   
6 / 2 (3) = x   
   
Now what? Do we divide 6 by 2 first, or multiply 2 with 3 first?   
If you follow what's called "implied multiplication", then you would multiply 2 with 3 first, since there is no multiplication sign.    
With implied multiplication, " 1/2x " would be the same as " (1/2) * x "   
Without implied multiplication " 1/2x " would be the same as " 1 / (2x) "   
So if x was equal to 4, " 1 / 2x " could be both (1/2) * x = 2   or   1 / (2x) = 0.125   
The same way, 6 / 2 ( 1 + 2 ) could both be:   
6 / 2 ( 1 + 2 ) = x     <=>   
6 / 2 (3) = x     <=>   
6 / 6 = x     <=>   
1 = x   
with implied multiplication, or   
6 / 2 ( 1 + 2 ) = x     <=>   
3 ( 1 + 2 ) = x     <=>   
3 ( 3 ) = x     <=>   
9 = x   
Without implied multiplication.
6 / 2 ( 1 + 2 ) = x <=>
6 / 2 (3) = x

Now what? Do we divide 6 by 2 first, or multiply 2 with 3 first?
If you follow what's called "implied multiplication", then you would multiply 2 with 3 first, since there is no multiplication sign.
With implied multiplication, " 1/2x " would be the same as " (1/2) * x "
Without implied multiplication " 1/2x " would be the same as " 1 / (2x) "
So if x was equal to 4, " 1 / 2x " could be both (1/2) * x = 2 or 1 / (2x) = 0.125
The same way, 6 / 2 ( 1 + 2 ) could both be:
6 / 2 ( 1 + 2 ) = x <=>
6 / 2 (3) = x <=>
6 / 6 = x <=>
1 = x
with implied multiplication, or
6 / 2 ( 1 + 2 ) = x <=>
3 ( 1 + 2 ) = x <=>
3 ( 3 ) = x <=>
9 = x
Without implied multiplication.
#52 - thesoulless (03/23/2013) [+] (19 replies)
The 2 outside of the brackets is a scalar, and as such it has to be applied to the brackets

6/2(1+2)=x
6/(2+4)=x or 6/2(3)
6/6=x
1=x


Now of course, it could be interpreted either way, because the equation in the content is pretty ambiguous, but the way I see it is the same way it is in my picture.
#403 - whateveridontneed (03/23/2013) [+] (6 replies)
only feasible answer is 1.

Assuming the following form: 6/(2b) where b = 1+2

If the answer is 9, it means that it would be 6/2 * b, where b= 1+ 2, which means that if the answer is indeed 9, the representation is wrong and thus the question itself is wrong.
#402 - rockyshand (03/23/2013) [-]
The point of this photo was to point out the retard that thinks 3x3 is 12 and not 9. But instead it starts a math flamewar.
User avatar #398 - therealslim (03/23/2013) [+] (2 replies)
7?
because when you use the distribution method
you multiply 2(1+2) so it would be 6 / 2 +4
so 3 + 4
#405 to #398 - bluetwizzler (03/23/2013) [-]
If you did it that way, you would still work with everything in the parentheses.
You would multiply 2 by 1 and the second 2.
Making 6 / (2+4)
Making it 6 / 6
Making the answer 1.
#372 - anonexplains (03/23/2013) [+] (4 replies)
Okay for all you tards here, the answer is 9. Don't try to discuss because it is 9.
Not 1
Not 12
Not 6
6/2 comes BEFORE 2(1+2) therefore -> 6/2 FIRST and THEN 3*(3) = 9
^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^
ONLY CORRECT ANSWER. OTHER ANSWERS ARE WRONG. L2MATHS TY.
#401 to #372 - bluetwizzler (03/23/2013) [-]
The answer is 1. The order of operations. PEMDAS. Look it up.
#371 - tomnash (03/23/2013) [+] (1 reply)
the answers 9. No debate, I did this kind of stuff when i was about 12
#392 to #371 - yourmomsfacehere (03/23/2013) [-]
the answers 12. no debate, I did this kind of stuff when i was about 9
User avatar #30 - donutzrawsum (03/23/2013) [+] (46 replies)
The reason you're all getting this wrong is not how you read the problem but how you are reading the numbers. 6/2(1+2) is not 6 / (2*1+2*2). When you divide by 2 you are essentially multiplying by .5 the /2 essentially means it is X or in this case 6 * 1/2 Which if you remember is 6 OVER 2, or 6/2. But that aside, replace the /2 for it's real value of * .5 and you see a different story.

TL;DR 6/2(1+2)= 6* .5(1+2). From here on what you may read it from any direction
6* (.5+1) or 6*1.5=9 I distributed the .5
3 (1+2) or 3+6 I multiplied first then distributed
Or because it's all multiplication and the order effectively doesn't matter anymore you can distribute the 6 instead
.5 * (6 + 12)=.5*18=18/2=9
User avatar #72 to #68 - SuitUp (03/23/2013) [-]
I weep for the American education system if you are it's offspring.

Try inputting the square of a negative number into your calculator. Depending on the model, but pretty likely, you'll get the number squared but negative. For that matter, if you don't have a decent calculator with a complex numbers mode, try rooting a negative number. Calculators have quirks and in those cases you unfortunately are required to engage your brain.

Now, I am prepared to acknowledge WHY you think it should be 9 and in fact the person that posed the question may also have intended for it to be 9. However whether the intent was there or not is irrelevent because the syntax is therefore incorrect.
(6/2)*(1+2) =9 which is what you are doing.
6/(2+4) = 1 which is as written in the initially posed question.

I have no doubt that the answer given by your teacher will have been from your gargled posing of the initial problem. Or he's non-existent/simply too busy to give any answer other than the one to make you go away.
User avatar #94 - happygrowman (03/23/2013) [+] (14 replies)
6/2(1+2)

6/2 + 6+4

3+1,5

4,5
User avatar #127 to #105 - Crusader (03/23/2013) [-]
6/2*3=
3*3 =
9

You go left to right if there are multiple sections that require the same stage of BEDMAS
#359 - IncarceratedNinja (03/23/2013) [-]
PEMDAS. Thats all you need. its not hard people.
#312 - Steinwolf (03/23/2013) [-]
So it begins..
#271 - anonexplains (03/23/2013) [+] (7 replies)
(6/2)(1+2)=9
there arent any brackets around the 6/2 so answer is 1
#291 to #289 - lolkingik (03/23/2013) [-]
Thank you for not being totally ******* retarded
#253 - dafuckisthisshit (03/23/2013) [-]
MFW the comments
User avatar #218 - supamonkey (03/23/2013) [-]
Needs another set of brackets.
#185 - fitemeirl (03/23/2013) [+] (21 replies)
Alright guys, playtime's over
#239 to #193 - smoklax (03/23/2013) [-]
Sorry mate, but he's right.
Also math is universal, it might learned or taught differently in places, but there is only one result that is correct, and thats 1.
Stop giving red thumbs, butthurt much?
#152 - decionetow (03/23/2013) [+] (4 replies)
whatever is in the Parentheses  has to be finished first

x = 6 / 2 ( 1 + 2 )

x = 6 / 2 ( 3 ) ---> the "3" is still in the Parentheses , and Parentheses  has to be finished first, so now we multiply it by the "2"

x = 6 / 6

x = 1
User avatar #162 to #152 - ewowo (03/23/2013) [-]
You're wrong, because the 2 is outside the parentheses.

6/2(3) is EXACTLY the same as 6/2x3.
User avatar #9 - Ropyx (03/22/2013) [+] (10 replies)
don't get me wrong, but i think is actually nine,
operations in expressions are done in this order:

Division/Moltiplication, then Addiction and subtraction

Divisions and Moltiplications are done in the order in which they are presented,

so, being the expression 6/2(1+2)
6/2(3)

"Divisions and Moltiplications are done in the order in which they are presented"

3(3)
= 9
User avatar #10 to #9 - skrynox (03/22/2013) [-]
It's actually 1. Just remember PEMDAS.
6/2(1+2) - Parentheses first
6/2(3) - Multiply (3) and 2 because there is no sign in between and parentheses is involved so it overrides the left to right.
6/6 - Divide
1 - TADA
#6 - improbablyyourdad ONLINE (03/22/2013) [+] (1 reply)
I don't mind when people get it wrong considering its easy to forget pemdas but &quot;3x3=12&quot;, really???
I don't mind when people get it wrong considering its easy to forget pemdas but "3x3=12", really???
[ 427 comments ]
Leave a comment
 Friends (0)